Near‐seabed sediment dynamics and fluxes on Chatham Rise, the effects of seabed disturbance, and implications for deep‐sea bottom trawling and seabed mining - Scott D. Nodder; Christopher A. Eager; Joe O’Callaghan; Daniel Leduc; Sam Davidson; Stacy Deppeler; Grace Frontin‐Rollet; Peter Gerring; Sarah Searson; William Quinn; Steve George; Ron Ovenden; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
Anthropogenic impacts are increasingly affecting deep‐sea environments, including seafloor sediment disturbances by bottom trawling and seafloor mining. Fieldwork in the ‘Resilience Of Benthic Ecosystems to Sedimentation’ (ROBES) project were conducted in 2018–2020 on the 400 m‐deep Chatham Rise crest, eastern Aotearoa New Zealand. Water column turbidity data, sediment traps on near‐seabed moorings and benthic landers and surficial sediments from multi‐corers provided baseline and post‐impact information following an artificially induced seafloor disturbance event in June 2019 using a modified harrow plough in and around an elongated bathymetric depression, designated as the ‘Butterknife’. During the disturbance, total mass and particulate organic carbon (POC) near‐bed fluxes were elevated above long‐term fluxes (2018–20). Long‐term 2018–19 fluxes were generally less than in 2019–20, driven by interannual oceanographic variations. These results, coupled with 50–100 m‐thick benthic boundary layers, suggest that lateral advection is a dominant process in the resuspension and redistribution of seafloor sediments on the rise. Further research is required to better understand the longer term dynamics of particle transport and deposition in response to human activities, such as bottom trawling or proposed phosphorite seafloor mining, especially in bathyal environments, such as the Chatham Rise.

Bioturbation and faunal-mediated ecosystem functioning in a deep-sea benthic community recovering from a severe seabed disturbance - Rachel Hale; Katharine T. Bigham; Ashley A. Rowden; Jane Halliday; Scott D. Nodder; Alan R. Orpin; Grace Frontin-Rollet; Katherine L. Maier; Joshu J. Mountjoy; Matthew H. Pinkerton (Deep Sea Research Part I: Oceanographic Research Papers, 2024)